PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIKA PADA SISWA KELAS VII SEMESTER II SMP NEGERI 17 MATARAM DALAM PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN INQUIRY PADA POKOK BAHASAN SEGITIGA - Nirmala, Baiq Aulia Purwanti; Juliangkary, Eliska; Yuliyanti, Sri (Media Pendidikan Matematika, 2018)
This research is a classroom action research that aims to improve the communication skills of mathematics in mathematics learning through inquiry approach at VIIth-B grade of SMPN 17 Mataram. This study was conducted in two cycles. The results showed that communication skills math class VII-B SMPN 17 Mataram increased from cycle I to cycle II after conducted inquiry learning approach. This is shown by as much as 74.28% of 36 students has increased at a total score of aspects of mathematical communication skills. To score every aspect of communication skills of mathematics shows that as much as 51.42% of the total number of students has increased on aspects of the capability of providing a rational reason to a statement, as much as 45.71% of 36 students has increased the ability to change aspects of description into a mathematical model, 71.43% of 36 students has increased the viability illustrate mathematical ideas in the form of a relevant description. The average value of the test in the first cycle was 61.03 in the category of medium and the second cycle increased to 67.66 in the high category. Based on the analysis of learning through observation sheets inquiry approach shows that the average percentage of enforceability in the first cycle is 80% and the second cycle increased to 94%. Data from these observations are confirmed by the data from interviews and data from the questionnaire responses of students to learning through inquiry approach which has increased from the first cycle o the second cycle for each aspect and are in the high category. Thus, students have responded positively to the learning of mathematics through inquiry approach as an effort to improve the communication skills of mathematics.